Adaptability of the tongue during orthodontic apparatus treatment - Maria B. Vasilyeva; Nidjat A. Guseynov (RUDN Journal of Medicine, 2023)
To date, most dentoalveolar deformities are associated with bad habits such as thumb sucking, tongue sticking out, and so on. According to the authors, protrusion of the tongue is normal in newborns, in which the tongue lies between the gingival pads, and the lower jaw is stabilized by the facial muscles during swallowing. With the eruption of temporary teeth, this physiological phenomenon disappears. The authors pointed out that there are such concepts as «simple tongue push» and «complex tongue push». The first relates to open bite push-outs. The second is observed in children with an open bite, as well as with respiratory complications and / or with a history of chronic diseases of the nasopharynx. The act of swallowing in the physiological sense is divided into 3 stages: oral, pharyngeal and esophageal. Each stage is characterized by different positions of the tongue in the oral cavity. Orthodontic hardware treatment of such patients is aimed at eliminating these habits, as well as correcting the bite. Although many studies have been conducted since 1965, to this day, aimed at studying the tongue protrusion in infantile swallowing, as well as in various malocclusion deformities, the authors found that these studies have shortcomings. For each patient, the shape, size, as well as the trajectory of movements may vary due to anatomical features (short frenulum of the tongue). In this review article, the authors consider such concepts as the adaptive ability of the tongue during infantile swallowing, as well as its trajectory of movements when using various methods of hardware treatment; various orthodontic devices for the treatment of tongue misalignments, their components and their purposes are described. The current classification, main characteristics of this pathological condition and its connection with the dentoalveolar system are considered. Based on the study, it can be concluded that there are several directions in the treatment of infantile swallowing. One of these areas is hardware treatment in the form of the use of plates with a flap for the tongue.